Holokaust: rewitalizacja ukraińskiej pamięci? W osiemdziesiątą rocznicę wydarzeń w Babim Jarze - Matusiak, Agnieszka (Iudaica Russica, 2021)
Presented text is a research reconnaissance on the Ukrainian memorial discourse on the Holocaust carried out in Babi Yar in September 1941. Author of the article focuses primarily on the period after the Revolution of Dignity, which became a turning point in Ukrainian-Jewish relations. The subject of special attention are two competitive commemorative projects that are being implemented by Memorial Museum of the Victims of Babi Yar and Memorial Holocaust Center “Babi Yar” (BYHMC).